A sugar planter's home, Serge island estate, St. Thomas, Jamaica. ([London] : [publisher not identified], 1924)
A black and white frontal view of the Serge island estate, St. Thomas.
Digitized
Keywords: Sugar factories -- Jamaica; Buildings -- Jamaica; Postcards -- Jamaica